The Influence of the Role of Religious Routine activities in Shaping the Religious Character Values of 5th Grade Elementary School Students: The Role of Religious Routines in Shaping 5th Grade Students' Religious Character - Irmayatus Sa'adah; Dya Ayu Agustiana Putri (Primary Education Insight, 2025)
Education plays a fundamental role in shaping future generations who are intellectually competent and morally grounded. In Indonesia, curriculum reforms such as the Independent Curriculum (Kurikulum Merdeka) have been introduced to foster these values ​​through intracurricular activities, the Pancasila Student Profile Strengthening Project (P5), and extracurricular programs. One key component of the P5 initiative is the instillation of religious character, which aligns with the first principle of Pancasila. This study examines the influence of religious activities on students' religious character. This type of research is quantitative with a habituation method. This study was chosen to measure the relationship between the independent and dependent variables. Data analysis techniques in this study were adjusted to the type of approach and research hypothesis. This study involved 55 fifth-grade students divided into two groups, namely the experimental and control classes. Data were collected through pretests and posttests, which were then analyzed using the T-test to test the hypothesis. The results showed a significant difference between the experimental and control classes, with a p-value <0.001 indicating that the role of religious ritual activities positively affects students' religious character.